Multisensory dysfunction accompanies crossmodal plasticity following adult hearing impairment - Meredith, M. Alex (2012)
Until now, cortical crossmodal plasticity has largely been regarded as the effect of early and complete sensory loss. Recently, massive crossmodal cortical reorganization was demonstrated to result from profound hearing loss in adult ferrets (Allman et al., 2009a). Moderate adult hearing loss, on the other hand, induced not just crossmodal reorganization, but also merged new crossmodal inputs with residual auditory function to generate multisensory neurons. Because multisensory convergence can lead to dramatic levels of response integration when stimuli from more than one modality are present (and thereby potentially interfere with residual auditory processing), the present investigation sought to evaluate the multisensory properties of auditory cortical neurons in partially deafened adult ferrets. When compared with hearing controls, partially-deaf animals revealed elevated spontaneous levels and a dramatic increase (~2 times) in the proportion of multisensory cortical neurons, but few of which showed multisensory integration. Moreover, a large proportion (68%) of neurons with somatosensory and/or visual inputs was vigorously active in core auditory cortex in the absence of auditory stimulation. Collectively, these results not only demonstrate multisensory dysfunction in core auditory cortical neurons from hearing impaired adults but also reveal a potential cortical substrate for maladaptive perceptual effects such as tinnitus.